1998
DOI: 10.1016/s0969-2126(98)00034-3
|View full text |Cite
|
Sign up to set email alerts
|

Human theta class glutathione transferase: the crystal structure reveals a sulfate-binding pocket within a buried active site

Abstract: hGST T2-2 shares less than 15% sequence identity with other GST classes, yet adopts a similar three-dimensional fold. The C-terminal extension that blocks the active site is not disordered in either the apo or complexed forms of the enzyme, but nevertheless catalysis occurs in the crystalline state. A narrow tunnel leading from the active site to the surface may provide a pathway for the entry of substrates and the release of products. The results suggest a molecular basis for the unique sulfatase activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
153
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 50 publications
6
153
0
2
Order By: Relevance
“…Position 9 of the consensus sequence is a serine, but the corresponding position is Ala-122 in Ure2p. In the known structures of theta class GSTs (38,44,45), this serine's O␥ atom is either positioned, or may be positioned through a simple change of rotamer, to form a hydrogen bond with the sulfhydryl group of bound glutathione (GSH). This interaction has been proposed to stabilize the GSH as a thiolate anion, and thus activate GSH for the nucleophilic addition of the GSH sulfur atom to electrophilic groups of hydrophobic substrates (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Position 9 of the consensus sequence is a serine, but the corresponding position is Ala-122 in Ure2p. In the known structures of theta class GSTs (38,44,45), this serine's O␥ atom is either positioned, or may be positioned through a simple change of rotamer, to form a hydrogen bond with the sulfhydryl group of bound glutathione (GSH). This interaction has been proposed to stabilize the GSH as a thiolate anion, and thus activate GSH for the nucleophilic addition of the GSH sulfur atom to electrophilic groups of hydrophobic substrates (43).…”
Section: Resultsmentioning
confidence: 99%
“…This interaction has been proposed to stabilize the GSH as a thiolate anion, and thus activate GSH for the nucleophilic addition of the GSH sulfur atom to electrophilic groups of hydrophobic substrates (43). Mutation of this catalytic serine, Ser-11, to alanine in the A. thaliana theta class GST not only dramatically reduced activity to less than 0.5% the wild-type enzyme, but also significantly reduced the mutant's affinity for immobilized GSH (45). In the other GST classes, the hydroxyl group of a conserved tyrosine serves to stabilize the thiolate anion.…”
Section: Resultsmentioning
confidence: 99%
“…residue near its active site (46,47). That class of the enzyme has poor CDNB conjugating activity and does not adhere to GSH affinity matrices, but uniquely exhibits sulfatase activity with 1-menaphthylsulfate as a substrate.…”
mentioning
confidence: 99%
“…That class of the enzyme has poor CDNB conjugating activity and does not adhere to GSH affinity matrices, but uniquely exhibits sulfatase activity with 1-menaphthylsulfate as a substrate. For the class Theta enzyme it was proposed that electrostatic interactions between the Arg 107 residue and the intermediate leaving sulfate group could be important for activity (47). It should be noted that the rate-limiting step for CDNB conjugation catalyzed by a blowfly class Theta enzyme which lacks an active-site tyrosine residue was also shown to be viscosity-dependent (48).…”
mentioning
confidence: 99%
“…3A), such that amino acids 1-231 are derived from the rat enzyme, whereas the final 13 amino acids correspond to residues 228-240 of the human GST. Modeling based on the homologous theta-class hGSTT2-2 crystal structure (27) indicated that the majority of the Cterminal helix of RH-A5 is derived from hGSTT1-1. Similarly, ITCHY clone RH-F2 contained a single 3Ј C͞O (Fig.…”
Section: Resultsmentioning
confidence: 99%